Biallelic Loss‐of‐Function NDUFA12 Variants Cause a Wide Phenotypic Spectrum from Leigh/Leigh‐Like Syndrome to Isolated Optic Atrophy. Issue 2 (3rd January 2022) - Magrinelli, Francesca; Cali, Elisa; Braga, Vinícius Lopes; Yis, Uluç; Tomoum, Hoda; Shamseldin, Hanan; Raiman, Julian; Kernstock, Christoph; Rezende Filho, Flávio Moura; Barsottini, Orlando Graziani Povoas; Taylor, Robert W.; Østergaard, Elsebet; et al.
Abstract: Background: Biallelic loss‐of‐function NDUFA12 variants have hitherto been linked to mitochondrial complex I deficiency presenting with heterogeneous clinical and radiological features in nine cases only. Objectives: To fully characterize, both phenotypically and genotypically, NDUFA12 ‐related mitochondrial disease. Methods: We collected data from cases identified by screening genetic databases of several laboratories worldwide and systematically reviewed the literature. Results: Nine unreported NDUFA12 cases from six pedigrees were identified, with presentation ranging from movement disorder phenotypes (dystonia and/or spasticity) to isolated optic atrophy. MRI showed basal ganglia abnormalities ( n  = 6), optic atrophy ( n  = 2), or was unremarkable ( n  = 1). All carried homozygous truncating NDUFA12 variants, three of which are novel. Conclusions: Our case series expands phenotype–genotype correlations in NDUFA12 ‐associated mitochondrial disease, providing evidence of intra‐ and inter‐familial clinical heterogeneity for the same variant. It confirms NDUFA12 variants should be included in the diagnostic workup of Leigh/Leigh‐like syndromes – particularly with dystonia – as well as isolated optic atrophy.